The Need to Have a Valid and Reliable Tool to Measure the Anatomy Education Environment - Tg. Fatimah Murniwati, Tg. Muda; Siti Nurma Hanim, Hadie@Haji; Asma', Hassan (2013)
Anatomy is an important knowledge for medical practice. Insufficient anatomy knowledge leading to errors in identification of anatomical structures during medical practices has been reported in many countries. Many medical students seem to have difficulties in learning anatomy and retaining the knowledge for future practice, thus this might reflect the possible flaws in anatomy education. In order to achieve optimum anatomy education environment and to close the gaps in education, measuring the students’ perception on anatomy teaching and learning is a pre-emptive measure needed by educationists. At present, there is no valid and reliable inventory available to specifically evaluate the anatomy education environment. Therefore, this article highlights the importance of having such inventory.